Reflux of nasopharyngeal content into middle ear through the eustachian tube - (:unkn) unknown (SPRINGER, 2004)
Whether nasopharyngeal content passes into the middle ear in patients without any head and neck pathology during the recovery phase of anesthesia is shown with an objective and prospective method. Thirty-eight patients, 21 female and 17 male, aged between 17 and 76, were included in the study. During the recovery phase of general anesthesia, 10 ml of 5 mCi Tc-99m-MAA was administered intranasally to the patients with a 10-F catheter. A manometer-adapted cuffed intubation tube was placed in the nasal passage so that the cuff was located at the choana. The pressure changes reflecting to the nasopharynx were recorded. The patients were extubated 10 min after the radionuclide was applied. The scintigraphic evaluation was done at the end of the 1 st hour of the application of radionuclide. Transmission and emission views were taken with a gamma camera. Passage of nasopharyngeal content into the middle ear via the eustachian tube was not a statistically significant observation. The mean value of maximum pressure reflecting from the nasopharynx did not differ significantly between patients. Our study does not support the hypothesis that nasopharyngeal content passes directly through the eustachian tube into the middle ear and causes deleterious effects.
Keywords: eustachian tube; eustachian tube dysfunction; reflux of nasopharyngeal content; middle ear; GASTROESOPHAGEAL-REFLUX; OTOLARYNGOLOGIC MANIFESTATIONS; VENTILATION SCINTIGRAPHY; PH; CHILDREN; INFANTS; DISEASE